2015
DOI: 10.1149/2.0021513jes
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vinylene Carbonate and Fluoroethylene Carbonate on SEI Formation on Graphitic Anodes in Li-Ion Batteries

Abstract: Binder free (BF) graphite electrodes were utilized to investigate the effect of electrolyte additives fluoroethylene carbonate (FEC) and vinylene carbonate (VC) on the structure of the solid electrolyte interface (SEI). The structure of the SEI has been investigated via ex-situ surface analysis including X-ray Photoelectron spectroscopy (XPS), Hard XPS (HAXPES), Infrared spectroscopy (IR) and transmission electron microscopy (TEM). The components of the SEI have been further investigated via nuclear magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
173
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(190 citation statements)
references
References 31 publications
14
173
0
Order By: Relevance
“…Figure 1 shows the current profile (a) and the gas evolution (b) of 12 + . While the current signal includes processes like capacitive currents related to the electrode surface or PF 6 − intercalation into the graphitic domains of the conductive carbon, which is reported to start around 4.6 V vs. Li/Li + , 25,26 we believe that the evolution of gaseous electrolyte oxidation products is a more meaningful indicator for the onset of electrolyte oxidation. As expected, Figure 1b shows that the oxidative CO 2 -release of VC starts at significantly lower potentials (∼4.3 V vs. Li/Li + ) compared to EC (∼4.8 V vs. Li/Li + ).…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Figure 1 shows the current profile (a) and the gas evolution (b) of 12 + . While the current signal includes processes like capacitive currents related to the electrode surface or PF 6 − intercalation into the graphitic domains of the conductive carbon, which is reported to start around 4.6 V vs. Li/Li + , 25,26 we believe that the evolution of gaseous electrolyte oxidation products is a more meaningful indicator for the onset of electrolyte oxidation. As expected, Figure 1b shows that the oxidative CO 2 -release of VC starts at significantly lower potentials (∼4.3 V vs. Li/Li + ) compared to EC (∼4.8 V vs. Li/Li + ).…”
Section: Resultsmentioning
confidence: 89%
“…[14][15][16][17] In order to investigate the onset potential for VC oxidation and its products, we performed on-line electrochemical mass spectrometry on electrolytes based on only VC or EC mixed with 1 M LiPF 6 . For these experiments, we used carbon black electrodes made from isotopically labelled 13 Ccarbon, so that we can track the gas evolution from the unlabeled 12 C-electrolyte by monitoring the corresponding 12 C-related signals of CO 2 and CO. 22 As Jung et al 24 recently showed that the onset and extent of electrolyte oxidation on LNMO and carbon black is identical, it is safe to transfer the results obtained from the 13 C-carbon model electrodes to real LNMO cathodes later on.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations